Classification of the etiologies of acute liver failure in Japan: A report by the Intractable Hepato‐Biliary Diseases Study Group of Japan. Issue 4 (17th February 2014) - Mochida, Satoshi; Takikawa, Yasuhiro; Nakayama, Nobuaki; Oketani, Makoto; Naiki, Takafumi; Yamagishi, Yoshiyuki; Fujiwara, Keiichi; Ichida, Takafumi; Tsubouchi, Hirohito
<x xml:space="preserve">Abstract</x> The Intractable Liver Diseases Study Group of Japan, supported by the Ministry of Health, Labor and Welfare, established novel diagnostic criteria for "acute liver failure" in 2011. In these criteria, patients without histological findings of hepatitis are included in the disease entity of "acute liver failure", as in Europe and the USA. In this report, classification criteria for the etiologies of "acute liver failure" in Japan are proposed.